Special Education in Brazil - from exclusion to inclusion - Maria Teresa Eglér Mantoan (Universidade Estadual de Campinas, 2000)
This article is about the phases through which the Brazilian education has been developing, starting from the exclusion of students with disabilities in specialized institutions which are typically therapeutically oriented to our present days, when this educational modality has been clashing with the proposals of a school for all, one and only, open to the differences, and, as a result, inclusive. The path that has been followed is focused on from the point of view of legal documents, of educational plans and policies. Finally we focus on teacher education and present some indicators by which we have been evaluating the benefits of inclusion in the Brazilian schools, through the investigations from the researchers at LEPED (Laboratory of Studies and Research in Teaching and Diversity) / Unicamp- São Paulo/Brazil.